1993
DOI: 10.1159/000204364
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of BCR/ABL Abnormalities in mRNA from 20-Year-Old Paraffin-Embedded Tissue for BCR/ABL Rearrangement by Polymerase Chain Reaction

Abstract: We studied whether it is possible to obtain sufficient mRNA from old paraffin-embedded samples of spleen and bone marrow for reverse transcription and polymerase chain reaction analysis. Spleen tissue from 6 subjects with chronic myelogenous leukemia was studied for rearrangement of BCR and ABL genes. Analysis was successful in 4 cases. These data indicate the feasibility of retrospective analysis of tissue samples of special interest by molecular techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…A model disease where molecular studies are of significant practical relevance is chronic myelogenous leukemia (CML), which is characterized by the hallmark Philadelphia chromosome caused by the t(9;22) translocation resulting in a breakpoint cluster region-Abelson (BCR-ABL) fusion. Already more than 10 years ago, up to two-decade-old archival tissues were demonstrated to be suitable for detection of BCR-ABL hybrid genes and fusion transcripts [3]. In accordance with these data, the successful detection of BCR-ABL transcripts also has been shown in other reports [40,41].…”
Section: Molecular Diagnostics In Myeloproliferative Disorderssupporting
confidence: 68%
“…A model disease where molecular studies are of significant practical relevance is chronic myelogenous leukemia (CML), which is characterized by the hallmark Philadelphia chromosome caused by the t(9;22) translocation resulting in a breakpoint cluster region-Abelson (BCR-ABL) fusion. Already more than 10 years ago, up to two-decade-old archival tissues were demonstrated to be suitable for detection of BCR-ABL hybrid genes and fusion transcripts [3]. In accordance with these data, the successful detection of BCR-ABL transcripts also has been shown in other reports [40,41].…”
Section: Molecular Diagnostics In Myeloproliferative Disorderssupporting
confidence: 68%
“…However, RT-PCR amplification of RNA from this material is a complex procedure that may be adversely influenced by several factors, mainly by nucleic acid breakdown during tissue processing and storage (Aurer et al, 1993). A recent extensive analysis of human and viral genes in FFPE tissue sections showed that amplification can be achieved most consistently by using primers that encompass small (less than 200 bp) RNA targets .…”
Section: Soguero Et Almentioning
confidence: 99%
“…The ability of ionizing radiations to cause contiguous double-stand DNA breaks proximity of BCR and ABL1 in the interphase nucleus and detection of BCRABL1 transcripts in leukemia cells from atomic bomb survivors with CML. CML developing in these persons began when they were exposed to radiations from the A-bombs [3,4]. If we accept this hypothesis we can estimate (minimally) the interval from developing BCR-ABL1 to the diagnosis of chronic phase CML.…”
Section: Introductionmentioning
confidence: 99%